A Descriptive Study On The Vocabulary Mastery of Tenth Year Students Of SMK Al Maksum Stabat - Lestari, Neneng; Yunita Sari Adelina; Edi Suprayetno (Fakultas Ilmu Pendidikan Universitas Sari Mutiara Indonesia, 2022)
This study deals with the discussion of vocabulary. The problem in this research is